Upaya Guru Mata Pelajaran Agama dalam Meminimalisir Prokrastinasi Akademik Siswa Madrasah Tsanawiyah Al Muttaqin Kota Pekanbaru - Nuraini; Gusma Afriani (Lembaga Anotero Scientific Pekanbaru, 2023)
This research aimed at finding out how the efforts of religious subject teachers in minimizing student academic procrastination at Islamic Junior High School of Al-Muttaqin Pekanbaru City were. It was a qualitative research. Observation, interview, and documentation were the techniques of collecting data. The data analysis technique was done through the steps of data reduction, data display, and drawing conclusions. The data validity was tested through data triangulation technique-comparing data from various sources to obtain the validity of the research findings. The research findings showed that some efforts carried out by the religious subject teachers in minimizing the behavior of academic procrastination were giving punishment, using various learning methods, giving motivation before and after the teaching and learning process, cooperating and communicating among religious subject teachers. The supporting factors were the support from the school and the cooperation among religious subject teachers and homeroom teachers in minimizing student procrastination behavior. The obstructing factors were the lack of student motivation and participation interest in learning, the lack of social support from the family, and the influence of peers.